Дано:
cos α = -1/√26
α ∈ ( π/2 ; π )
Найти:
sin α
• Выразим через основное тригонометрическое тождество синус:
sin² α + cos² α = 1
sin² α = 1 - cos² α
sin α = √(1 - cos² α)
• Так как α ∈ ( π/2 ; π ), то α ∈ II четверти, где sin α > 0
sin α = √(1 - (-1/√26)²) = √(1 - 1/26) = √(25/26) =
5/√26 = 5√26/26
ответ: sin α = 5√26/26
Дано:
cos α = -1/√26
α ∈ ( π/2 ; π )
Найти:
sin α
• Выразим через основное тригонометрическое тождество синус:
sin² α + cos² α = 1
sin² α = 1 - cos² α
sin α = √(1 - cos² α)
• Так как α ∈ ( π/2 ; π ), то α ∈ II четверти, где sin α > 0
sin α = √(1 - (-1/√26)²) = √(1 - 1/26) = √(25/26) =
5/√26 = 5√26/26
ответ: sin α = 5√26/26